Alternative intronic promoters in development and disease - Vacik, Tomas; Raska, Ivan (Protoplasma, 2017)
Approximately 20,000 mammalian genes are estimated to encode between 250 thousand and 1 million different proteins. This enormous diversity of the mammalian proteome is caused by the ability of a single-gene locus to encode multiple protein isoforms. Protein isoforms encoded by one gene locus can be functionally distinct, and they can even have antagonistic functions. One of the mechanisms involved in creating this proteome complexity is alternative promoter usage. Alternative intronic promoters are located downstream from their canonical counterparts and drive the expression of alternative RNA isoforms that lack upstream exons. These upstream exons can encode some important functional domains, and proteins encoded by alternative mRNA isoforms can be thus functionally distinct from the full-length protein encoded by canonical mRNA isoforms. Since any misbalance of functionally distinct protein isoforms is likely to have detrimental consequences for the cell and the whole organism, their expression must be precisely regulated. Misregulation of alternative intronic promoters is frequently associated with various developmental defects and diseases including cancer, and it is becoming increasingly clear that this phenomenon deserves more attention.
Keywords: Protein Isoforms; messenger RNA; Developmental defects; jednonukleotidový polymorfismus; Introns; alternativní sestřih; Transcriptional regulation; Promoter Regions, Genetic; Exons; genetické nemoci vrozené; Gene expression; Transcription, Genetic; genetická transkripce; Alternative promoters; RNA, Messenger; zvířata; protein - isoformy; Alternative Splicing; Genetic Diseases, Inborn; Humans; promotorové oblasti (genetika); introny; Protein isoforms; Human diseases; exony; lidé; Polymorphism, Single Nucleotide; Animals